Neutralization of pro‐inflammatory monocytes by targeting TLR2 dimerization ameliorates colitis. (16th February 2016) - Shmuel‐Galia, Liraz; Aychek, Tegest; Fink, Avner; Porat, Ziv; Zarmi, Batya; Bernshtein, Biana; Brenner, Ori; Jung, Steffen; Shai, Yechiel
Abstract: Monocytes have emerged as critical driving force of acute inflammation. Here, we show that inhibition of Toll‐like receptor 2(TLR2) dimerization by a TLR2 transmembrane peptide (TLR2‐p) ameliorated DSS‐induced colitis by interfering specifically with the activation of Ly6C + monocytes without affecting their recruitment to the colon. We report that TLR2‐p directly interacts with TLR2 within the membrane, leading to inhibition of TLR2–TLR6/1 assembly induced by natural ligands. This was associated with decreased levels of extracellular signal‐regulated kinases (ERK) signaling and reduced secretion of pro‐inflammatory cytokines, such as interleukin (IL)‐6, IL‐23, IL‐12, and IL‐1β. Altogether, our study provides insights into the essential role of TLR2 dimerization in the activation of pathogenic pro‐inflammatory Ly6C hi monocytes and suggests that inhibition of this aggregation by TLR2‐p might have therapeutic potential in the treatment of acute gut inflammation. Synopsis: Here, we utilize a novel strategy to neutralized TLR2 activation by inhibiting its dimerization by TLR2 transmembrane‐derived peptide (TLR2‐p). We show that TLR‐2 peptide ameliorated DSS‐induced colitis by interfering specifically with the activation of Ly6C + monocytes without affecting their recruitment to the colon. The TLR2 transmembrane‐derived peptide (TLR2‐p) inhibits TLR2 signaling by interacting with its reciprocal receptors within the membrane. TLR2‐p inhibits the dimerization of TLR2–TLR6/1 induced by natural ligands, resulting in attenuation of pro‐inflammatory downstream signaling. Inhibition of TLR2 dimerization ameliorates acute colitis. TLR2‐p inhibits TLR2 signaling in pathogenic pro‐inflammatory Ly6C hi monocytes without affecting their recruitment to the inflamed gut. Abstract : A novel approach for blocking TLR2 signaling modulates immune cell activation and reduces disease severity during acute gut inflammation.